# [Tex/LaTex] Increase the spacing of rows in equations

amsmathline-spacingmath-modemathtools

I have a formula and I want to increase the space between the rows to make the reading easier.

\begin{flalign*} \epsilon \bm{\Xi}_n & = M_\epsilon(\bm{x}_{\epsilon,n-1} ) - M(\bm{x}_{n-1}) = \\ &=M_\epsilon(\bm{x}_{\epsilon, n-1} ) - M(\bm{x}_{\epsilon, n-1} ) + M(\bm{x}_{\epsilon,n-1})-M^n(\bm{x}) = \\ &=\epsilon \bm{\xi}_n + M( M(\bm{x}_{\epsilon, n-2} ) +\epsilon \bm{\xi}_{n-1}) - M^n(\bm{x}) = \\ &=\epsilon \bm{\xi}_n + \epsilon DM(\bm{x}_{n-1}) \bm{\xi}_{n-1}+ M^2\left( M(\bm{x}_{\epsilon, n-3} + \epsilon \xibf_{n-2} \right) -M^n(\bm{x}) + O(\epsilon^2) \\ & = \epsilon \bm{\xi}_n + \epsilon DM(\bm{x}_{n-1})\bm{\xi}_{n-1}+\epsilon DM^2( \bm{x}_{n-2}) \bm{\xi}_{n-2} + M^3( \bm{x}_{\epsilon, n-3} )-M^n(\bm{x}). \end{flalign*}


I read this post Temporarily increase line spacing but there are a lot of different methods. Some of ones works only for text.

I use the following packages:

\usepackage{ws-rotating}
\usepackage{graphicx}
\usepackage{epstopdf}
\usepackage[utf8]{inputenc}
\usepackage{amsmath}
\usepackage{mathtools}


If you want to increase row spacing uniformly in a multiline group of equations without having to type [vertical spacing] at each line break, you can use \setstretch (from the \setspace package) at the beginning of such an environment. Btw, if you load mathtools, you don't have to load amsmath. Also, I think what you need is the aligned environment, rather than flalign*, which doesn't work with equation.

The second example in the example is typeset with \setstretch{2}:

\documentclass{article}
\usepackage[utf8]{inputenc}
\usepackage[T1]{fontenc}
\usepackage{fourier}
\usepackage{heuristica}
\usepackage{mathtools}
\usepackage{bm}
\usepackage{setspace}

\begin{document}

\begin{aligned} \epsilon \bm{\Xi}_n & = M_\epsilon(\bm{x}_{\epsilon,n-1} ) - M(\bm{x}_{n-1}) = \\ &=M_\epsilon(\bm{x}_{\epsilon, n-1} ) - M(\bm{x}_{\epsilon, n-1} ) + M(\bm{x}_{\epsilon,n-1})-M^n(\bm{x}) = \\ &=\epsilon \bm{\xi}_n + M( M(\bm{x}_{\epsilon, n-2} ) +\epsilon \bm{\xi}_{n-1}) - M^n(\bm{x}) = \\ &=\epsilon \bm{\xi}_n + \epsilon DM(\bm{x}_{n-1}) \bm{\xi}_{n-1}+ M^2\left( M(\bm{x}_{\epsilon, n-3} + \epsilon \bm{\xi}_{n-2} \right) -M^n(\bm{x}) + O(\epsilon^2) \\ & = \epsilon \bm{\xi}_n + \epsilon DM(\bm{x}_{n-1})\bm{\xi}_{n-1}+\epsilon DM^2( \bm{x}_{n-2}) \bm{\xi}_{n-2} + M^3( \bm{x}_{\epsilon, n-3} )-M^n(\bm{x}). \end{aligned}

\setstretch{1.5}\begin{aligned} \epsilon \bm{\Xi}_n & = M_\epsilon(\bm{x}_{\epsilon,n-1} ) - M(\bm{x}_{n-1}) = \\ &=M_\epsilon(\bm{x}_{\epsilon, n-1} ) - M(\bm{x}_{\epsilon, n-1} ) + M(\bm{x}_{\epsilon,n-1})-M^n(\bm{x}) = \\ &=\epsilon \bm{\xi}_n + M( M(\bm{x}_{\epsilon, n-2} ) +\epsilon \bm{\xi}_{n-1}) - M^n(\bm{x}) = \\ &=\epsilon \bm{\xi}_n + \epsilon DM(\bm{x}_{n-1}) \bm{\xi}_{n-1}+ M^2\left( M(\bm{x}_{\epsilon, n-3} + \epsilon \bm{\xi}_{n-2} \right) -M^n(\bm{x}) + O(\epsilon^2) \\ & = \epsilon \bm{\xi}_n + \epsilon DM(\bm{x}_{n-1})\bm{\xi}_{n-1}+\epsilon DM^2( \bm{x}_{n-2}) \bm{\xi}_{n-2} + M^3( \bm{x}_{\epsilon, n-3} )-M^n(\bm{x}). \end{aligned}

\end{document}